Policy Tools DP3AP2KB West Sumatera Province in the Family Quality Improvement Program in Improving Family Resilience in Padang City - Putra, Alex; Sasmita, Siska (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The high divorce rate and domestic violence (KDRT) are indications of weak family resilience. The government has a policy of presenting the Family Quality Improvement Program which is one form of government effort to improve family resilience. This research aims to examine the use of policy tools used by DP3AP2KB of West Sumatra Province in the Family Quality Improvement Program to strengthen family resilience in Padang City. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the research indicate that the most used policy tools in program implementation are laws and regulations and direct service provision, which are the main foundations in achieving program objectives. In addition, the use of transfer payments and intergovernmental grants was also found as a complement, while other policy tools such as outbound contracts out, tax systems, loans and loan guarantees, and insurance were not practically used. The research conclusions emphasize the importance of selecting and implementing policy tools appropriate to the social context, and show that informal and flexible approaches can still be effective in implementing social programs.